Alcohol-Directed ortho-C–H Alkenylation - Li, Li; Liu, Qinglan; Chen, Jiean; Huang, Yong (Synlett, 2019)
We report a simple and mild dehydrogenative cross-coupling reaction of unprotected arylethanols and acrylates. Unlike the case of previous reactions, in which prior functionalization of the substrate with a metal-coordinating site was required, free primary, secondary, or tertiary hydroxy groups were found to be effective directing groups for the ortho-C–H palladation and subsequent olefination.
Keywords: directing group; palladium catalysis; cross-coupling; C–H activation; arylethanols; acrylates